Profiles of Nutrition and Non – Nutrition Factors Related to Anemia Status Among Lactating Mothers in Jakarta - Reisa Melisa Wijaya; Diana Aulia; Saptawati Bardosono (World Nutrition Journal, 2019)
Background and Objective: Anemia is a major health problem affecting every phase of life. However less attention given to lactating mothers where anemia can give bad impacts to the mothers themselves and their babies. Less knowledge also known about nutrition and non-nutrition factors related to anemia. Therefore, this study aims to profile nutrition and non-nutrition factors related to anemia status among lactating mothers.Method: This cross-sectional study was conducted in Grogol Petamburan and Cilincing Public Health Centre in Jakarta in February–April 2019. Seventy fours lactating mothers aged 20–35 years old who delivered within the last 3–6 months recruited using consecutive sampling method. Nutrition factors examined were energy, protein, iron, folate, vitamin B6, vitamin B12, vitamin C intakes, and body mass index (BMI). Non-nutrition factors examined were level of education and family income. Basic characteristic data was collected by interview and dietary intake was assessed using a semiquantitative-food frequency questionnaire and 24-hours food recall for two non-consecutive days. BMI and laboratory assessments (haemoglobin, ferritin serum, and c-reactive protein) were done.Results: Anemia prevalence was 8% and 11% was iron deficient. Prevalence of iron deficiency anemia was 3% (37.5% from prevalence of anemia). Based on Indonesia Recommended Dietary Allowance, around 58% subjects had low iron intake, 39% with low vitamin B6 intake, 27% with low vitamin B12 intake, 40% with low vitamin C intake, and no subject with low folate intake. Around 53% of subjects had BMI < 22.9 kg/m2. Almost 70% of the subjects had middle level of education and 50% had family income lower than regional minimum wage.Conclusion:  Prevalence of anemia among lactating mothers in Jakarta was 8%. Non-nutrition factors had higher proportion compared to nutrition factors related to anemia status. Further studies are needed to determine the possible causes of anemia in lactating mothers.